PERMODELAN TRANSPORT KADMIUM (Cd) DAN NIKEL (Ni) DALAM LINDI MENGGUNAKAN SOFTWARE POLLUTE V7 (STUDI KASUS: TPA SANGGRAHAN, TEMANGGUNG) - Lintang Tyas Perdana; Badrus Zaman; Mochtar Hadiwidodo (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Sanggrahan Landfill (Temanggung), completed with gravel, geotextile, geomembrane, and compacted clay. It’s still has potential of contaminant mobilization through those liners that comes from solid waste in landfill. The purposes of this research for knowing the movement cadmium (Cd) and nickel(Ni) in leachate vertically in every depth. The contaminant movement from active zone head for control 1-well and from active zone head for control 2-well could be predicted by using model pollute v7 software. Pollute v7 is one dimension model, where needed the characteristic of the liners (depth, permeability, porosity, dry density, coef dispersion of hydrodinamics). This model describe the contaminant mobilization affected by dispersion, advection, diffusion, and retardation phenomenon. Based on 12 years forward model simulation in this study, the concentration of Cd and Ni will get increase. The results showed, value of cadmium concentration in control 1-well is 0,496 mg/l and in control 2-well is 0,4064 mg/l. Whereas, the value of nickel concentration in control 1-well is 0,382 mg/l and in control 2-well is 0,3665 mg/l. This prediction showed that Sanggrahan Landfill has potential in leachate mobilization. The study suggests that the application of geomembrane should has lower permeability than 0,5x10-12m/s for retarding contaminant transport.